2010
DOI: 10.5751/ace-00391-050201
|View full text |Cite
|
Sign up to set email alerts
|

Declines of Aerial Insectivores in North America Follow a Geographic Gradient

Abstract: North American birds that feed on aerial insects are experiencing widespread population declines. An analysis of the North American Breeding Bird Survey trend estimates for 1966 to 2006 suggests that declines in this guild are significantly stronger than in passerines in general. The pattern of decline also shows a striking geographical gradient, with aerial insectivore declines becoming more prevalent towards the northeast of North America. Declines are also more acute in species that migrate long distances c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
248
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(274 citation statements)
references
References 47 publications
(41 reference statements)
9
248
3
1
Order By: Relevance
“…Here, we examine nest box occupancy rates of Tree Swallows to evaluate whether these data suggest spatiotemporal patterns of population changes. We also evaluate whether these data produce conclusions similar to those of Nebel et al (2011). Similar results from both sources of data would add credence to patterns reported by Nebel et al (2011).…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Here, we examine nest box occupancy rates of Tree Swallows to evaluate whether these data suggest spatiotemporal patterns of population changes. We also evaluate whether these data produce conclusions similar to those of Nebel et al (2011). Similar results from both sources of data would add credence to patterns reported by Nebel et al (2011).…”
Section: Introductionsupporting
confidence: 56%
“…Previous studies have suggested that populations of North American aerial avian insectivores are decreasing (Robbins et al 1989, Böhning-Gaese et al 1993, Askins 1995 Nebel et al (2011) concluded that Tree Swallow (Tachycineta bicolor) populations were among the species of decreasing aerial insectivores, especially in northeastern North America. BBS data, such as those analyzed by Nebel et al (2011), are collected along roads, and are most concentrated near areas of high human population density (see Sauer et al 2011 for details on spatiotemporal coverage).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most negative trends have occurred in Canada and the northern USA since the late 1960s, while more southern breeding populations have remained stable or have slightly increased (Sauer et al 2012), and these trends appear to be characteristic of most aerial insectivores breeding in North America (Nebel et al 2010, NABCI Canada 2012. This situation provides a useful comparative paradigm whereby the strength of migratory connectivity can be investigated across regions with different population trends.…”
Section: Introductionmentioning
confidence: 99%
“…North American breeding populations of Barn Swallow have decreased drastically in recent decades but causes of declines remain largely unknown (Cadman et al 2007, McGowan and Corwin 2008, Nebel et al 2010, Bird Studies Canada et al 2012. Most negative trends have occurred in Canada and the northern USA since the late 1960s, while more southern breeding populations have remained stable or have slightly increased (Sauer et al 2012), and these trends appear to be characteristic of most aerial insectivores breeding in North America (Nebel et al 2010, NABCI Canada 2012.…”
Section: Introductionmentioning
confidence: 99%